EDUKASI PEMBATASAN CAIRAN PADA PASIEN DENGAN PENYAKIT GINJAL KRONIK YANG MENJALANI HEMODIALISA DI RS DR. BRATANATA JAMBI - Andini, Febri Tri; Anjeli, Anjeli (Jurnal Ilmu-Ilmu Kesehatan, 2024)
Chronic Kidney Disease (CKD) is a progressive and irreversible decline in kidney function where decreased kidney function causes the kidneys to be unable to maintain a balance of metabolism, fluids and electrolytes which can result in uremia. Therefore respondents who undergo hemodialysis need to limit fluid intake. Without limiting fluid intake, fluid will accumulate and cause edema around the body. To inform people of knowledge of chronic kidney disease patients who have hemodialysis by providing education on fluid boundary. The study use descriptive method, the sample on this study to screen 1 person a client with CKD that had hemodialysis, by using questionnaire’s index before and after an educational measure and a media leaflet. Thee result obtained by researcher in the hemodialysis client CKD show there are differences , which before providing client only was able to answer 4 of the 10 of  questionnaires, after providing the manager of fluid the client was able to answer 8 of 10 questions. Beside that the client also able to make an essay to re explain by researcher. The conclusion is by giving education  on fluid restriction to CKD client has very much a bearing on knowing of the precipitation of client having hemodialysis.